The Warsaw Ghetto : a guide to the perished city - Engelking, Barbara 1962- (Yale Univ. Press, 2009)
"The establishment and subsequent liquidation of the Warsaw Ghetto has become an icon of the Holocaust experience, yet, remarkably, a full history of the ghetto has never been written, despite the publication over some sixty years of numerous memoirs, studies, biographical accounts, and primary documents. The Warsaw Ghetto: A Guide to the Perished City is this history, researched and written with painstaking care and devotion over many years and now published for the first time in English." "In this book the authors explore the history of the ghetto's evolution, detailing the daily experience of its thousands and thousands of inhabitants from its creation in 1941 to its liquidation in 1943. Encyclopedic in scope, the book encompasses a range of topics from food supplies to education, religious activities to the structure of the Judenrat. Separate chapters deal with the mass deportations to Treblinka in July 1942 and the famous uprising in April 1943. Detailed original maps identify the locations of businesses, social institutions, medical facilities, and more, while biographical notes, a glossary of terms, and an extensive bibliography complete this masterful work of restoration."--BOOK JACKET